The Strategy of Cash Waqf Development for Financing Farmers - Niswah, Farokhah Muzayinatun; Assadam, Elvina (ZISWAF, 2023)
An important Indonesian social-based Islamic financial instrument is known as Waqf, with a flexible cash financing scheme specifically prioritized. This flexible instrument has enormous potential and enables more productivity when used according to the existing community needs in Indonesia. One of the productive developments is also known as waqf for micro-farmer business capital, which assists middle to lower-class people commonly depending on crops and experiencing financial problems. From the description, waqf is capable of assisting farmers in production activities through a productive project program. This program requires the essential formulation of appropriate strategies, expressing the need for standard implementation improvement. Therefore, this study aimed to analyze the priority strategies implemented to optimize waqf for financing farmers in Lamongan. A mixed qualitative and quantitative approach was implemented through the Analytic Network Process (ANP), as data were obtained from interviews with seven waqf and agriculture experts. The results showed that the primary strategy focused on the establishment of synergies between the government and the community, increased literacy regarding the urgency of waqf to the public, and improved farmer businesses through coaching and mentoring. This analysis was used as a reference in establishing policies for the Indonesian Waqf Board, the Department of Food Security and Agriculture, and the local government, specifically in Lamongan.